2022
DOI: 10.3389/fnbeh.2022.909512
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture at GV20 and ST36 Improves the Recovery of Behavioral Activity in Rats Subjected to Cerebral Ischemia/Reperfusion Injury

Abstract: Traditional acupuncture and electroacupuncture (EA) have been widely performed to treat ischemic stroke. To provide experimental support for the clinical application of acupuncture to ameliorate post-stroke sequelae, in this study, we investigated the therapeutic effect of acupuncture and EA on CIRI following middle cerebral artery occlusion (MCAO) in rats. The animals were randomly divided into five groups: sham-operated (S), model (M), traditional acupuncture (A) treatment, electroacupuncture (EA) treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…Several studies have proven the significant neuroprotective effect of the widely used acupoints ST36 and GV20 in the management of neurological diseases 35–37 . Specifically, the ST36 has proven to be beneficial in alleviating chronic pain 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have proven the significant neuroprotective effect of the widely used acupoints ST36 and GV20 in the management of neurological diseases 35–37 . Specifically, the ST36 has proven to be beneficial in alleviating chronic pain 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proven the significant neuroprotective effect of the widely used acupoints ST36 and GV20 in the management of neurological diseases. 35 , 36 , 37 Specifically, the ST36 has proven to be beneficial in alleviating chronic pain. 38 Consistent with previous findings, we found that EA stimulation acupoints at ST36 and GV20 markedly decreased pain hypersensitization induced by CCI surgery, with the anti‐nociceptive effect increased in a time‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle is the main target of Adipo and a major location of AdipoR1. Although skeletal muscle is considered to be one of the targets of pharmacological treatment for IR or diabetes ( Dong et al, 2021 ; Wei et al, 2021 ; Yu et al, 2022 ), some studies have shown that acupuncture ST36 may stimulate skeletal muscle and improve the recovery of behavioral activity in rats subjected to cerebral ischemia or reperfusion injury ( Yang et al, 2022 ). Sun demonstrated that acupuncture at ST36 increased motor cortical excitation ( Sun et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical and basic studies have shown that electroacupuncture (EA) at Baihui (GV20) and Zusanli (ST36) is effective in treating cerebral ischemia, but its mechanism is still unclear [ 11 , 12 ]. At present, there has been no research report on the neuroprotective effect of EA on pMCAO secondary hypothalamic injury by regulating the 5-HT/5-HT2A signal pathway.…”
Section: Introductionmentioning
confidence: 99%